Technical assistance needs for realizing person-centered thinking, planning and practices in United States human service systems. Issue 3 (12th October 2020) - Croft, Bevin; Petner-Arrey, Jami; Hiersteiner, Dorothy
Abstract : Purpose: The United States' National Center on Advancing Person-Centered Practices and Systems provides technical assistance to human service systems on person-centered thinking, planning and practices. To apply for the Center's technical assistance, 33 state human service systems submitted applications and participated in interviews in which they detailed technical assistance needs. This technical paper examines themes that emerged from these technical assistance applications and interviews. These themes offer a view into barriers, obstacles and priorities for human service systems as they work toward more person-centered practices. Common themes point to key areas that, if enhanced, could result in a more person-centered system overall. Design/methodology/approach: The application process generated 33 applications containing technical assistance goals and priorities, summaries of recent and ongoing initiatives to advance person-centered approaches, measurement methods and anticipated challenges. Using thematic analysis, the authors organized the information into seven themes. Findings: Applicants identified seven themes to improve person-centered thinking, planning and practices: Staff Training and Competencies, Participant Engagement, Measurement and Quality Improvement, Cross-System Consistency in Planning and Practice, Payment and Managed Care, Cultural and Linguistic Responsiveness and Other Practice-Related Goals. They also articulated contextual factors that help or hinder systems efforts and a vision for an ideal person-centered system. Originality/value: The themes provide a unique window into human service system administrators' priorities for achieving more person-centered human service systems and the conditions that may promote or hinder systems change.